Coagulation factor XII protease domain crystal structure. (11th March 2015) - Pathak, M.; Wilmann, P.; Awford, J.; Li, C.; Hamad, B. K.; Fischer, P. M.; Dreveny, I.; Dekker, L. V.; Emsley, J.
Summary Background Coagulation factor XII is a serine protease that is important for kinin generation and blood coagulation, cleaving the substrates plasma kallikrein and FXI. Objective To investigate FXII zymogen activation and substrate recognition by determining the crystal structure of the FXII protease domain. Methods and results A series of recombinant FXII protease constructs were characterized by measurement of cleavage of chromogenic peptide and plasma kallikrein protein substrates. This revealed that the FXII protease construct spanning the light chain has unexpectedly weak proteolytic activity compared to β‐FXIIa, which has an additional nine amino acid remnant of the heavy chain present. Consistent with these data, the crystal structure of the light chain protease reveals a zymogen conformation for active site residues Gly193 and Ser195, where the oxyanion hole is absent. The Asp194 side chain salt bridge to Arg73 constitutes an atypical conformation of the 70‐loop. In one crystal form, the S1 pocket loops are partially flexible, which is typical of a zymogen. In a second crystal form of the deglycosylated light chain, the S1 pocket loops are ordered, and a short α‐helix in the 180‐loop of the structure results in an enlarged and distorted S1 pocket with a buried conformation of Asp189, which is critical for P1 Arg substrate recognition. The FXII structures define patches of negative charge surrounding the active site cleft that may be critical for interactions with inhibitors and substrates. Conclusions These data provide the first structural basis for understanding FXII substrate recognition and zymogen activation.